GASTROINTESTINAL ENZYME ACTIVITY OF YELLOWFIN TUNA LARVAE (Thunnus albacares) - Kasful Anwar; Gunawan Gunawan; Mugi Mulyono; Ofan Bosman; Muhamad Husnan (Indonesian Aquaculture Journal, 2026)
Knowledge of morphological development, digestive system, and digestive enzymes in larvae is key to developing optimal larval and seedling maintenance strategies. The purpose of this study was to determine the digestive system and digestive enzyme activity in yellowfin tuna (Thunnus albacares) larvae cultivated in hatcheries. Yellowfin tuna eggs were spread in concrete tanks measuring 3x2x1.2 m (volume 6 m³), with 90,000 eggs per tank. The analysis of digestive enzymes in yellowfin tuna larvae in this study included protease, amylase, and lipase enzymes. Digestive enzyme analysis method using a spectrophotometer with a wavelength of 340–560 nm. Enzyme analysis was performed on tuna eggs and larvae at stages D-1, D-4, D-7, D-10, D-15, and D-20. The results showed that the digestive enzyme activity of yellowfin tuna (protease, amylase, and lipase) was detected while still in the egg stage and was also detected in D-1 larvae. The emergence of digestive enzymes is triggered by internal mechanisms related to the development of the digestive system. The presence of all digestive enzymes (protease, amylase, and lipase) in yellowfin tuna larvae indicates the importance of these enzymes in early development.